Factors affecting behavior Intention to Adopt Mobile Learning by Middle East University Students' in Jordan: Based on UTAUT Model - Altawalbeh, Dr. Manal A. (Opción, 1970)
This study aimed to investigate the factors affecting students' intention to adopt mobile learning at Middle East University in Jordan. The study sample consisted of (120) undergraduate students selected randomly from faculty of educational science in Middle East University (MEU) for the second semester in the academic year 2018-2019. The study results showed that there is a positive and significant impact of performance expectance, effort expectance and social influence on behavioral intention of students to adopt m-learning. T-test analysis results also indicated non-significant differences in BI between male and female students. One-way ANOVA revealed no significant difference in BI to adopt m-learning among students at different age levels.